2012
DOI: 10.1016/j.avsg.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Functional Status Following Amputation After Lower Extremity Bypass

Abstract: Background Some patients who undergo lower extremity bypass (LEB) for critical limb ischemia ultimately require amputation. The functional outcome achieved by these patients after amputation is not well known. Therefore, we sought to characterize the functional outcome of patients who undergo amputation after LEB, and to describe the pre- and perioperative factors associated with independent ambulation at home after lower extremity amputation. Methods Within a cohort of 3,198 patients who underwent an LEB be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 22 publications
6
64
0
Order By: Relevance
“…Consensus recommendations cite revascularization as the optimal treatment for patients with CLI20 given the poor prognosis21 and functional impairment22 following major amputation. Allie et al23 reported that 51% of CLI patients had no diagnostic vascular evaluation preceding primary amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus recommendations cite revascularization as the optimal treatment for patients with CLI20 given the poor prognosis21 and functional impairment22 following major amputation. Allie et al23 reported that 51% of CLI patients had no diagnostic vascular evaluation preceding primary amputation.…”
Section: Discussionmentioning
confidence: 99%
“…4, 7, 9, 10, 16-18 Patients who are unlikely to survive past thirty days would benefit from non-operative management rather than undergo the AKA, which is often associated with significant deleterious psychological and physical sequelae. 5, 6, 9, 10 Moreover, even if patients with a poor prognosis pre-operatively do survive to discharge, they are unlikely to have a successful functional outcome. 6 Conversely, patients who have a low risk for 30-day mortality are more likely to have a meaningful and more independent functional status.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6, 9, 10 Moreover, even if patients with a poor prognosis pre-operatively do survive to discharge, they are unlikely to have a successful functional outcome. 6 Conversely, patients who have a low risk for 30-day mortality are more likely to have a meaningful and more independent functional status. 19, 20 …”
Section: Discussionmentioning
confidence: 99%
“…Among ambulatory patients with critical limb ischemia and without a history of prior major amputation, ambulation rates following infrainguinal bypass are 97 percent [2][3] but are only 20 percent among those with such a history [4]. Previous reports suggest a comparable disadvantage following major amputation: whereas about 55 percent of those undergoing nontraumatic major lower-limb amputation remain ambulatory [5] only about 38 percent of those with a prior history of contralateral limb loss remain ambulatory following loss of the second lower limb [6].…”
Section: Introductionmentioning
confidence: 85%